Letramento crítico multimodal no ensino de língua portuguesa: investigando os memes compartilhados no facebook - Oliveira, Erika Guimarães de (2019)
Considering the multimodal characteristic of discursive genres (KRESS; van LEEUWEN, 2006), the study of how the various semiotic elements are related is important because it allows the interaction between the elements that make up the different senses or meanings in the communicative spheres. This perspective of multimodality and critical view on a language, that is, the multimodal critical literacy (LCM in Portuguese), has been approached by authors such as (BUZATO, 2007, MOTTA-ROTH; LOVATO, 2009, PREDEBON, 2015). This research is focused on the study of multimodal critical literacy in Portuguese language classes based on shared memes in social networks. The memes present in our daily lives are seen as elements of fun and entertainment, but can also be used as a learning tool. They circulate in digital spaces such as Facebook, promoting interaction and communication, especially from humor, in shared comments on social networks. The challenge of pedagogical practice is to associate memes' humor with teaching in general and, in this specific research, with teaching Portuguese language. Our objective is to investigate how LCM in Middle School students is characterized, considering the pragmatic-discursive elements that constitute political and educational memes and the discourses derived from the students' comments in social networks. We are supported by the discussions of Kress and van Leeuwen (2006) on multimodality and The Grammar of Visual Design (GDV in Portuguese), as well as in studies on critical literacy from Fairclough's Critical Discourse Analysis (ADC in Portuguese) (1989; 1997; 2001; 2003) developed from the Pedagogy of Multiliteracies (NEW LONDON GROUP, 1996; ROJO; MOURA, 2012). Based on the hypothesis that the development of LCM is recommended by formal education and, with this type of literacy, it is expected that the student: 1) expand the active domain of discourse in the various communicative situations; 2) increase their possibilities of social participation in the exercise of citizenship and 3) amplify the capacity for critical analysis. As specific objectives, we seek to describe the political and educational memes in social networks and analyze the prominent discourses that result from the comments about memes of Middle School students. For methodology, we propose a field research (digital), with a theoretical basis in multimodal analysis and critical discourse, which is explained by the need to consider different semiotic resources that constitute the meme, besides listing standardized elements that allow the separation into categories. We analyzed a corpus consisting of comments about memes, in a community created from a private account on the Facebook relationship site. In this research, we investigate how the LCM is contextualized from the results obtained, in the analysis of comments about memes, and we try to understand how the LCM happens in the understanding of the multimodal critical aspects in the daily life of the student, inside and outside the classroom.